(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the psychological impact of parental conflict and problematic situations in the family on children’s psyche. Disagreements, quarrels, and a conflictive environment in the family can negatively affect the emotional state, behavior, and social development of children. The study highlights the fear, anxiety, aggression, and self-doubt that arise in children due to parental conflict. It also emphasizes the importance of creating a positive atmosphere in the family for the healthy psychological development of children.